Criminal profiling then and now: prospect and challenges in Malaysia - Mustaffa, Maisarah; Md Said, Muhamad Helmi; Drs Nasrul, Muhammad Amrullah; Hassan, Muhamad Sayuti; Rajamanickam, Ramalinggam; Dahlan, Nur Khalidah (Ritchmann Publication, 2022)
The purpose of this article was to ascertain the concept of criminal profiling by taking into consideration the evolution of its definition, function, methodology and also the background of profiling officers from the beginning up to the present time. Using the critical and literature review approach, references from journals, books, statutes and international cases were analyzed to pinpoint the most recent developments to the criminal profiling method. While researches and literature reviews regarding criminal profiling were undoubtedly significant overseas, it was not the same case back in our homeland. Discussions were few and even then, not entirely focusing nor mentioning the procedures and practice of criminal profiling during investigation. It was also found that there seem to yet exist a clarity in regards to the definition and methodology of criminal profiling nor the background of profiler involved despite it being carried out during investigative process for a long period of time. This article also highlighted the challenges discovered in the practice of criminal profiling such as the vagueness of its method in our law, the existence of race-based profiling practice and the credibility of criminal profiling as an expert evidence in courts which was debatable due to the absence of any yardstick to determine the capability of a profiler.